Growth deficits in antiretroviral and HIV-exposed uninfected versus unexposed children in Malawi and Uganda persist through 60 months of age. (15th March 2022) - Fowler, Mary Glenn; Aizire, Jim; Sikorskii, Alla; Atuhaire, Patience; Ogwang, Lillian Wambuzi; Mutebe, Alex; Katumbi, Chaplain; Maliwichi, Limbika; Familiar, Itziar; Taha, Taha; Boivin, Michael J.
Abstract : Objective: To compare childhood physical growth among antiretroviral drug and maternal HIV-exposed uninfected (AHEU) compared with HIV-unexposed uninfected (HUU) children. Design: Longitudinal follow-up of PROMISE trial (NCT01061151) AHEU and age-matched and sex-matched HUU children, enrolled (September 2013 to October 2014) in Malawi and Uganda. Method: We compared WHO population standardized z -scores [height-for-age (HAZ), weight-for-age (WAZ), weight-for-height (WHZ), head-circumference-for-age (HCAZ) at 12, 24, 36, 48, and 60 months of age]. We evaluated HUU versus AHEU [in-utero combination antiretroviral treatment (cART) versus Zidovudine (ZDV) alone]; stratified by country, using longitudinal linear and generalized linear mixed models. Results: Of 466 Malawian and 477 Ugandan children, median maternal age at enrollment was 24.5 years (Malawi) and 27.8 years (Uganda); more than 90% were breastfed through 12 months except Uganda AHEU (64.0%). HAZ scores (adjusted for maternal age, breastfed, and socioeconomic status) were lower among AHEU versus HUU children at every time point, significant ( P < 0.05) among Ugandan but not Malawian children. Similar patterns were seen for WAZ but not for WHZ or HCAZ scores. High stunting was observed in both countries, significantly higher in Malawi; and higher among AHEU versus HUU children through 48 months of age, significantly ( P < 0.05) among Ugandan but not Malawian children. We found no differences in childhood growth trajectories with in-utero exposures to ZDV compared with cART. Conclusion: AHEU versus HUU children had lower median LAZ and WAZ scores persisting through 60 months of age. However, proportions of children with stunting or underweight decreased after 24 months of age.